2017
DOI: 10.1109/jbhi.2017.2653179
|View full text |Cite
|
Sign up to set email alerts
|

Saliency-Based Lesion Segmentation Via Background Detection in Dermoscopic Images

Abstract: The segmentation of skin lesions in dermoscopic images is a fundamental step in automated computer-aided diagnosis of melanoma. Conventional segmentation methods, however, have difficulties when the lesion borders are indistinct and when contrast between the lesion and the surrounding skin is low. They also perform poorly when there is a heterogeneous background or a lesion that touches the image boundaries; this then results in under- and oversegmentation of the skin lesion. We suggest that saliency detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 53 publications
1
79
0
1
Order By: Relevance
“…However, the application of saliency methods for segmentation of skin lesion is relatively new [13,17,37]. Saliency segmentation computes the most informative region in an image based on human vision perception such that salient and nonsalient parts become foreground region (skin lesion) and background region (healthy skin), respectively.…”
Section: Saliency Based Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of saliency methods for segmentation of skin lesion is relatively new [13,17,37]. Saliency segmentation computes the most informative region in an image based on human vision perception such that salient and nonsalient parts become foreground region (skin lesion) and background region (healthy skin), respectively.…”
Section: Saliency Based Segmentationmentioning
confidence: 99%
“…However, many of the improved saliency segmentation algorithms still face difficulty when salient objects share similar color features with the background pixels. These algorithms often lack the ability to effectively handle complicated images with low contrast [18,20,37]. Complementing the methods of saliency computation with other useful analysis methods such as the morphological analysis can significantly improve image segmentation results.…”
Section: Saliency Based Segmentationmentioning
confidence: 99%
“…Research in saliency by the computer vision research community has shown promising accuracy in object (feature) detection for medical images and scientific data [MTY*11, BMSH16, AKB*17]. These medical and scientific images tend to have salient object composition, that is differentiation between the foreground and background objects, for example, the lungs, heart, abdominal organs and bony skeleton are the foreground and empty space is the background.…”
Section: Related Workmentioning
confidence: 99%
“…Even experienced dermatologists may produce the inconsistent diagnosis results [7]. During recent decades, computer-aided diagnosis systems (CADs) have been developed and already demonstrated strengths for assisting dermatologists in enhancing their clinical diagnosis of melanoma [8], [9].…”
Section: Introductionmentioning
confidence: 99%